Epigrafia tra erudizione antiquaria e scienza storica Ad honorem Detlef Heikamp - Paolucci, Fabrizio (Studi e saggi, 2019)
Detlef Heikamp's is one of the greatest scholars of the collections of historical pieces in Florence; to celebrate his 90th birthday, on the 10th an 11th November 2017, a study meeting dedicated to the birth of epigraphy as historical science was organised. The Uffizi Galleries were the ideal setting for such an initiative: there, starting from the 17th century, one of the most valuable Greek and Latin epigraphy collections was created, and it would deeply mark the evolution of this field of study; it is precisely to this institution which Detlef Heikamp decided to donate a precious selection of finds from his collection of inscriptions, in the aftermath of a disastrous attack in 1993. The most authoritative experts in the sector participated enthusiastically in the two days in Florence; their ten contributions are now collected in this volume, which offers an updated and accurate picture of the excellence of Italian research in the field of Greek and Roman epigraphy.